α-admissible Prešić type operators and fixed points - Shukla, Satish; Shahzad, Naseer (Nonlinear Analysis: Modelling and Control, 2016)
In this paper, we introduce α-admissible mappings on product spaces and obtain fixed point results for α-admissible Prešić type operators. Our results extend, unify and generalize some known results of the literature. We also provide examples which illustrate the results proved herein and show that how the new results are different from the existing ones.
Keywords: α-admissible operator; Prešić type operator; fixed point